1998
DOI: 10.1007/s002210050326
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration lesions of the amygdala disrupt the rhinal corticothalamic projection system in rhesus monkeys

Abstract: In macaque monkeys, aspiration but not excitotoxic lesions of the medial temporal lobe limbic structures, the amygdala and hippocampus, produce a severe impairment in visual recognition memory. Furthermore, certain ventromedial cortical regions, namely the rhinal (i.e., entorhinal and perirhinal) cortex, are now known to be critical for visual recognition memory. Because the route taken by temporal cortical efferent fibers, especially perirhinal efferents, passes nearby the amygdala, it is possible that inadve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 42 publications
2
49
1
3
Order By: Relevance
“…Instead, damage to inferotemporal cortex appears to be responsible for the impairment (Baxter et al, 1999;. Together with evidence that aspirative removals of the amygdala disrupt the efferent projections of the rhinal cortex (Goulet et al, 1998), these findings indicate that damage to fibers passing near or through the amygdala, rather than loss of the cell bodies of the amygdala, accounts for some behavioral deficits observed after the aspirative removals. Given that lesions of rhinal cortex severely disrupt object reversal learning , it is possible that transection of rhinal cortical efferents, rather than amygdala damage, is responsible for the object reversal learning impairment seen after aspirative amygdala lesions.…”
Section: Introductionmentioning
confidence: 81%
“…Instead, damage to inferotemporal cortex appears to be responsible for the impairment (Baxter et al, 1999;. Together with evidence that aspirative removals of the amygdala disrupt the efferent projections of the rhinal cortex (Goulet et al, 1998), these findings indicate that damage to fibers passing near or through the amygdala, rather than loss of the cell bodies of the amygdala, accounts for some behavioral deficits observed after the aspirative removals. Given that lesions of rhinal cortex severely disrupt object reversal learning , it is possible that transection of rhinal cortical efferents, rather than amygdala damage, is responsible for the object reversal learning impairment seen after aspirative amygdala lesions.…”
Section: Introductionmentioning
confidence: 81%
“…The finding that the auditory memory of case Rh-2͞HϩPH was in fact preserved despite complete removal of the hippocampal system suggests a possible resolution of the contradiction, namely, that the impairment produced by the MT ablation resulted not from damage to the hippocampal system but from collateral damage, such as severing the projections of rSTG to downstream areas in the prefrontal cortex, medial thalamus, or both (e.g., see ref. 39). An anatomical study undertaken to examine this possibility (M. Munoz, M.M., and R.C.S., unpublished data) demonstrated that an MT removal does indeed disconnect rSTG anatomically from several prefrontal and medial thalamic areas.…”
Section: Discussionmentioning
confidence: 99%
“…A role for the amygdala in crossmodal sensory processing has been proposed on the basis that surgical extirpations of the amygdala impaired intermodal, but not intramodal, performance on a delay nonmatch to sample (DNMS) task (32). However, subsequent experiments involving neurotoxic lesions to the amygdala failed to find deficits, whereas lesions to the anterior rhinal cortex resulted in major deficits (33). In studies with humans, amygdala damage has failed to result in deficits of intermodal sensory processing (9), although this negative finding was thought to reflect the fact that none of the tasks involved sensory-affective associations.…”
Section: Discussionmentioning
confidence: 99%